Índice de Anomalias de Chuvas (IAC) para a sub-bacia hidrográfica do rio Sucuru, alto curso do rio Paraíba- PB - José Marcos Duarte Rodrigues; Eduardo Rodrigues Viana de Lima (Geopauta)
This study consists of analyzing rainfall variations in the Sucuru River sub-basin, upper Paraíba River, using the Rainfall Anomaly Index (IAC). For this purpose, rainfall data from 2000 to 2019, collected from the website of the Paraíba Water Management Executive Agency (AESA), were used to determine the annual IAC. Thus, it was noted that in the period from 2000 to 2011 there was a predominance of rainy to extremely rainy IAC and in the period from 2012 to 2019, there was a predominance of dry to extremely dry IAC. Therefore, it is concluded that the Sucuru River sub-basin is marked by long periods of drought, causing losses for the population.